Investigating Blasting Demolition Dust Micromorphology, Microscopic Agglomeration Process With Wetting Droplet and Suppression Effectiveness by Explosion Water Mist - Fu, Jiangtao; Hu, Lingling; Hu, Minghua (Frontiers in Environmental Science, 2022)
Blasting demolition has been widely used in the safe and efficient demolishing of construction buildings. Blasting demolition dust is the most visible and realistic harmful material during the blasting process. The characteristics and suppression of the blasting dust are scarcely addressed in the literature. This paper investigated the micromorphology characteristic of blasting demolition dust from a typical building demolition project. The dust median size value D50 was 65.890 μm, and it showed a character of smooth edge, fluffy structure, and cracks. It consists of higher content of heavy metals than conventional cement powder particles, which include Mn, Ni, Zn, and As elements. The dust can not be wet by municipal water for its hydrophobic character. A novelty method was proposed to set a methodology to form a stable, larger volume and surface area water droplet on a rod stand, which provided more opportunities to find out and verify the microscopic agglomeration phenomenon and effectiveness between dust and different wetting droplets. The single dust-droplet collision results can be accurately recorded by the high-speed camera with a microscope, the collision and submergence time between blasting demolition dust particle and municipal water droplet on the stand was 2 ms, while the time was 1.125 ms with surfactant solution droplet, it was much shorter than the time of municipal water. The dust-droplet microscopic collision results were shown that the blasting demolition dust can be better wet and agglomerated by a surfactant solution. In blasting demolition projects, the BDD suppression methods with surfactant solution explosion mist have the highest efficiency, which can restrict the BDD’s concentration to 10 mg/m3.